PREDIKTOR ASMA PADA USIA 7 TAHUN SETELAH MENDERITA BRONKIOLITIS AKUT KARENA RESPIRATORY SYNCYTIAL VIRUS: SUATU STUDI PROSPEKTIF - Kusuma, HMS. Chandra (Fakultas Kedokteran Universitas Brawijaya, 2006)
Infants are at increased risk of developing asthma after RSV (Respiratory Syncytial Virus) acute bronchiolitis. The hypothesis that cytokine production is related to the development of asthma after RSV bronchiolitis. The diagnosis of RSV bronchiolitis was verified using the Abbott test pack RSV, a rapid enzyme immuno assay for direct detection of viral antigen in nasopharyngeal secretion. Changes in FEV1 (Forced Expiratory Volume in 1 second) were determined using spirometri, IL-4 and IFN-γlevels were determined using the enzyme-linked immunosorbant assay (ELISA) method. In this study, 62 children hospitalized for RSV bronchiolitis were followed prospectively, 55 (88.7%) childrencompleted the study and 41 children (74.5%) had asthma at 7 years of age. RSV bronchiolitis children were more frequent among boys (boy /girl ratio: 2). Episodes of wheezing more than 8 had specifity and sensitivity of 100% respectivelly,might be the very useful predictor for asthma. The cut off level over 40.84 pg/ml for IL-4, below 14.12 pg/ml for IFN-γ, IL-4 / IFN-γratio over 3 and episodes of wheezing over 8 may be used to predict asthma after RCV bronchiolitis.